Comparative study of atrazine degradation by magnetic clay activated persulfate and H2O2. Issue 19 (20th March 2020) - Zong, Shaoyan; Xu, Ximeng; Ran, Gang; Liu, Jian
Abstract : To effectively remove the EDCs in water, Fe3 O4 was loaded on the surface of modified sepiolite clay by co-precipitation to catalyze K2 S2 O8 and H2 O2 respectively to generate SO4 ˙ − and ·OH for ATZ removal. Abstract : To effectively remove the endocrine disrupting chemicals (EDCs) in water, Fe3 O4 was loaded on the surface of modified sepiolite clay by the method of co-precipitation to catalyze potassium persulfate (K2 S2 O8 ) and hydrogen peroxide (H2 O2 ) respectively to generate SO4 ˙ − and ·OH for atrazine (ATZ) removal. The magnetic clay catalyst was characterized by XRD, SEM, N2 adsorption–desorption and isoelectric point. The degradation efficiency of ATZ in the two systems was systematically compared in terms of initial pH, oxidant dosage and oxidant utilization rate. The results revealed that, after 90 minutes, systems with K2 S2 O8 and H2 O2 can remove 65.7% and 57.8% of the ATZ under the given conditions (30 °C, catalyst load: 1 g L −1, initial pH: 5, [ATZ]0 : 10 mg L −1, [H2 O2 ]0 : 46 mmol L −1, [PDS]0 : 46 mmol L −1 ). The magnetic clay catalyst still maintained good catalytic activity and stability during the four consecutive runs. Based on the quenching experiments, it was demonstrated that the dominant radical species in the two systems were SO4 ˙ − /·OH and ·OH, respectively. However, the degradation efficiency of the two systems presented different responses toward the condition variations; the system with K2 S2 O8 was relatively more sensitive to solution pH, the oxidant efficiency was generally higher than that of the H2 O2 system (except 184 mmol L −1 ).